Analysis of OVO Merchant Satisfaction Levels at 5 Shopping Centers in Bandung City Based on the Kano Model - Stefhanie Ancela Lahallo; Elmor Benedict Wagiu (STMIK PONTIANAK, 2021)
In Industry 4.0, technological advances affect how to transact. Technological advances have created digital payment instrument that aim to make it easier for consumers to make payments. Many digital payments have been used by public. One of them is E-Wallet. An E-Wallet is a digital payment instrument; users must be connected to a server and connected to an Internet location. This study aims to analyze the indicators that affect level of merchant satisfaction, determine the service standards according to merchant desires, and determine OVO service quality improvement strategy using the kano model. This model aims to analyze indicators that affect the level of merchant satisfaction, based on how well the service level is able to satisfy merchant needs. This research begins with preliminary survey to determine the number of OVO merchants in 5 shopping centers in Bandung. Then data collection is done by distributing primary data (questionnaires) to OVO merchants at 5 shopping centers in Bandung.The results of the study show services that fall into the category of Performance Needs (O), Basic Needs (M), and Excitement Needs (A) affect the level of satisfaction. Services that fall into the Performance Needs (O) category are standart services in accordance with the wishes of OVO merchants. The improvement strategy that OVO needs to do to improve service quality is by increasing the indicators that are the basic needs of users.